General principles of EU law and the EU digital order - Bernitz, Ulf; Groussot, Xavier; Paju, Jaan; Vries, Sybe Alexander de, 1970- (European monographs ;, 2020)
General Principles of EU Law and the EU Digital Order' addresses the role of general principles in the era of digitalization and the (potential) impact of digitalization on the theory of general principles of union law. Digitalization of societies has important ramifications for citizens and businesses. The digital landscape is rapidly changing, whereas at the same time there are growing concerns about how market access in the European Union?s (EU?s) digital market as well as fundamental rights can be sufficiently safeguarded in the shadow of?big data? and algorithms. This book presents expert analyses of how digitalization raises questions of the future role for general principles of EU law, including the foundational principles of the EU?s fundamental economic freedoms and EU competition rules.